ANALISIS BIOMEKANIKA FOREHAND GROUNDSTRUKE ATLET YUNIOR DAERAH ISTIMEWA YOGYAKARTA - UNTUNG NUGROHO (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2015)
This study aims to reveal the technical performance of tennis forehand groundstrokes in DIY junior athletes. The study population was a junior tennis athletes DIY totaling 10 people male and female athletes aged 18 years maximum. Of the population is used as a sample. Sampling technique used in this study was purposive sampling criteria who attended the regional championships and national championships. The technique of the data analysis was descriptive and percentage with the calculation in every stage using the Dartfish software systems analysis Prosuite to know more clearly the performance of the forehand groundstroke technique carried out by DIY junior tennis athletes.The results show that the performance of the tennis forehand groundstrokes of DIY junior athletes is on good preparation stage, the backswing is quite good, forwardswing is quite good, the impact is quite good, and the followtrough is quite good. Overall, the performance DIY junior athletes on forehand groundstrokes in tennis is categorized quite good. Â